Modelamiento para el almacenamiento y aporte de energía a la red en horas pico de demanda mediante un prototipo - Jacho Topón, Pablo Daniel (2015)
This draft thesis develops a modeling allows to study the behavior of daily electricity demand residential with which the possibility of including a prototype storage and supply of energy, the model is programmed and presented at the MATLAB software tool analyzes ; first the behavior of the occupants of a dwelling is modeled by the Markov method and its respective power equivalent using the Monte Carlo method, the model obtained daily residential demand optimizes manually looking for a reference limit by which energy is obtained which provides the prototype and storing it at another time of day, another way to optimize energy presented in this study is entering an amount of money and that the model yield results that much energy is stored and provides network.